Intra-rectal use of epinephrine in radiotherapy of prostate cancer - Qin, Shang-Bin (Cancer Manag Res, 2019)
Purpose: The aim of the study was to evaluate the feasibility and toxicity of intra-rectal epinephrine during prostatic radiotherapy. Materials and methods: A total of 34 patients with prostate cancer were randomized to receive daily intra-rectal epinephrine (4 mg in 40 mL, n=16) or placebo (40 mL normal saline, n=18) 5 min before daily radiotherapy. Physical examination including systolic blood pressure (SBP) and heart rate (HR) was performed before, 5 min after, and 20 min after intra-rectal use. Toxicities were graded using the Radiation Therapy Oncology Group standard. A two-sided Fisher's exact test was used to compare proportions between groups. A mixed-effects model was used to analyze multiple measurements of SBP and HR. Survival curves were calculated using the Kaplan–Meier method and compared between groups using the log-rank test. Results: All patients completed the protocol treatment and reported no cardiovascular symptoms after intra-rectal administration. There were no differences in SBP and HR between these two groups at any time point (before, 5 min after, and 20 min after epinephrine). At 5 weeks after the start of radiotherapy, the incidence of rectal toxicity≥grade 2 was 27.8% (5/18) for the control group versus 12.5% (2/16) for the epinephrine group, but was not statistically significant (p=0.4). There was no rectal toxicity≥grade 2 in these two groups beyond 2-year follow-up. The 5-year biochemical relapse-free survival was 75.0% and 72.2% for the epinephrine and control group, respectively. Conclusion: Results of this pilot randomized trial have demonstrated that intra-rectal administration of epinephrine is feasible and safe in prostatic radiotherapy. Its radio-protective effect warrants further investigation.